Menumbuhkan Semangat Bela Negara Dan Cinta Tanah Air Melalui Pengabdian Masyarakat Pada Generasi Muda - Refni Yulia; Yudi Subiantoro; Livia Ersi; Risa Junita Sari; M. Satria Nugraha; Tri Hadinata (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This community service initiative was undertaken with the objective of cultivating a strong sense of national defense and patriotism among the younger generation. In the context of globalization, digitalization, and the pervasive influence of foreign cultures, young people are increasingly vulnerable to identity crises, diminished civic engagement, and limited participation in national life. To address these challenges, the program employed a qualitative approach, combining literature review with an analysis of community service as a form of social intervention. The findings indicate that strategies such as character education, active involvement in social activities, the integration of media and technology, and the internalization of Pancasila values and national history prove effective in fostering patriotic attitudes and enhancing youth participation in national defense. Moreover, the study underscores the importance of designing community service initiatives that are contextually relevant, participatory, and innovative. It further recommends that educational institutions, community organizations, and local governments align community service programs with civics education and digital platforms to strengthen civic consciousness and patriotism.